Decay and durability of building stones in urban environments - C. M. Grossi; R M. Esbert; F. Díaz-Pache (Materiales de Construccion, 1998)
This paper studies the effect of some pollutant agents in urban environments -gaseous SO2, acid rain and solid particles- on carbonate and siliceous building stones with different petrophysic characteristics. The selected environments have been London, Garston (UK) and Burgos (Spain) and the exposed materials have been Portland, Combe Down and Hontoria limestones, Laspra dolomite and Rosa Porriño granite. Products generated by the action of gases, acid rain and solid particles on stones have been analyzed. To point out the properties of stones that influence their decay, the results obtained on the stones exposed to the above environments have been compared to those from some laboratory accelerated ageing tests.